LCD cyclic codes over finite fields - Ahamd, BELOUADAH; Saad, LATRECHE; Supervisor: Lakhdar, HEBOUB (Mohamed Boudiaf University of M'sila, 2025)
In this memory, we have studied the concept of linear codes and linear cyclic codes. We then examined a particular subclass of these codes, Linear Complemented Dual cyclic codes over finite fields
Keywords: Linear codes; cyclic codes; LCD cyclic codes